Karakteristik Kimia dan Fisika Tanah di Area Pertanaman Nanas dengan Perbedaan Tingkat Produksi: Soil Chemical and Physical Characteristics in Pineapple Plantation with Different Rate of Yield - Rina Natalia; Syaiful Anwar; Atang Sutandi; Budi Nugroho; Priyo Cahyono (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2018)
Differences in productivity were observed in various land units on pineapple plantation in Central Lampung even with the same land and fertilization management. The nature of soil chemical and physical variability were thought to be the cause of these differences. The study was aimed to compare chemical and physical soil properties in land units with different pineapple productivity. Soil samples were taken from 6 units of land with low and 3 units of land with high productivity. The soil chemical properties measured include available P and K, potential P and K, total N, pH, organic C, exchangeable cations, and available micro nutrients. The soil physical properties determined include bulk density, soil texture, and penetration resistance. The data was analyzed using T-test and correlation. The T-test revealed that the high productivity soils were significantly lower in available P, potential P, total N, and available Zn compared to the productivity soils. Furthermore, the high productivity soils were significantly lower in bulk density and penetration resistances both vertically and horizontally. There were significantly negative correlations between pineapple yields with potential P, available Zn, bulk density, and penetration resistance both vertically and horizontally. Overall analyses indicating that the physical properties were more as productivity determinant, particularly bulk density and penetration resistance, compared to the chemical properties. The chemical properties were more as residual conditions after nutrient absorption process to support pineapple productivity. In order to increase the productivity, it is necessary to manage the soil to lower bulk density and penetration resistance.